Effect of systemic administration of granulocyte-colony stimulating factor on rate of fracture healing of bone defect in goats as animal model - Looi, Collin Seng Kim; Khairuddin, Nurul H.; Chen, Hui Cheng; Ramasamy, Rajesh; Lau, Seng Fong; A. Roohi, Sharifah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Granulocyte-colony stimulating factor (G-CSF) serves as an important cytokine in haematopoiesis; released at both physiological and pathological conditions by a range of cells. We hypothesized that the systemic administration of G-CSF would produce an accelerated fracture-healing rate in non-union bone defects; thus, potentially leading to useful clinical applications. Ten male adult Katjang goats, weighing about 15-26 kilograms were randomly chosen and a tibial bone defect was induced in each animal. The defect was maintained by internal fixation with a titanium plate and reinforced by an external fiberglass cast. Post-operative radiographs were performed twice weekly and radiographic assessments were performed by evaluating the bridging and union measurements through a validated method. In the treatment group, the time for bridging and union exhibited statistically significant differences when compared with a control group. The outcomes of the present study establishing a notion that administration of G-CSF besides inducing haematopoiesis, promotes healing of fractures and non-union bone defects as well.